2010
DOI: 10.1177/1049732309358325
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences of Their Violent Behavior in an Intimate Partner Relationship

Abstract: The purpose of this study was to describe women's perceptions of their violent behavior in a heterosexual partnership. The study followed the traditions of Husserlian descriptive phenomenology and the philosophy of existential phenomenology. Twenty-four volunteer Finnish women, aged 19 to 58 years, with a history of different manifestations of intimate partner violence (IPV) participated in open-ended interviews. The data were analyzed by the method developed by Colaizzi. The findings revealed that some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…In the United Kingdom, two women are killed every week by a current or former partner (Hester ). We acknowledge that domestic abuse can take place against men by women (Flinck & Paavilainen ), or within same‐sex relationships, but 90% of domestic abuse is committed by men against women (Department of Health ). For this reason, our research was concentrated on women survivors.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, two women are killed every week by a current or former partner (Hester ). We acknowledge that domestic abuse can take place against men by women (Flinck & Paavilainen ), or within same‐sex relationships, but 90% of domestic abuse is committed by men against women (Department of Health ). For this reason, our research was concentrated on women survivors.…”
Section: Introductionmentioning
confidence: 99%
“…The invisibility of violence to women is the result of several factors, including the trivialization and relativity of these actions, which may be viewed as natural [24]. Many women minimize the importance of their IPV experience [6,20].…”
Section: Discussionmentioning
confidence: 83%
“…The need to protect one's self or one's children is commonly cited in the literature as a motivation for female-perpetrated IPV (e.g., Flinck and Paavilainen 2010;Hamberger et al 1997;Langhinrichsen-Rohling et al 2012;Swan et al 2008). For example, in a study of male and female court-referred perpetrators, Hamberger et al (1997) found that women were more likely than men to report violence perpetration to protect themselves or to escape a situation in which their male partner was being violent.…”
Section: Violence As Self-defensementioning
confidence: 99%